Faktor–Faktor Yang Mempengaruhi Penerimaan Pajak Daerah di Provinsi Kalimantan Timur - Dimas Bagus Mahasinul Akbar; Indri Arrafi Juliannisa (Jurnal Indonesia Sosial Teknologi, 2022)
This study aims to determine the effect of Gross Regional Domestic Product (GDP), Total Population, Investment and Capital Expenditure on Regional Tax Revenue in Regencies/Cities in East Kalimantan Province. East Kalimantan Province is one of the provinces that has the highest level of regional tax revenue on the island of Kalimantan, recorded in 2016 - 2020 East Kalimantan has the highest tax revenue on the island of Borneo. This study uses panel data by combining time series and cross section data. The method in this study uses panel data regression analysis which can be used to measure the effect of the independent variable on the dependent variable. The results of this study indicate that population and investment have a significant positive effect, while GRDP and capital expenditures have no effect on local taxes. The results of the study simultaneously show that GRDP, population, investment and capital expenditures have an effect on local taxes.